The relationship between biochemical parameters, interleukin-6 and ovarian morphology in polycystic ovary syndrome. Issue 3 (2012) - Bostancı, Sühha Mehmet; Bayram, Merih; Sevinç, Faika Ceylan; Paşaoğlu, Hatice; Elbeğ, Şehri
No abstract available